Antibiotic Overuse in Paediatric Gastroenteritis: A descriptive cross-sectional study from Children’s Hospital: Antibiotic Overuse in Paediatric Gastroenteritis - Bharo, Mumtaz Ali; Bahalkani, Ubedullah; Kumar, Pardeep; Khuhro, Asif Ali; Shah, Iftikhar Haider; Zaki, Muhammad (Pakistan Journal of Health Sciences, 2025)
There is a major role of gastroenteritis in pediatric patients. Knowing about prescription trends is very useful in optimizing treatment and minimizing the use of unnecessary medication. Objective: To assess the frequency of antibiotic prescriptions in children with gastroenteritis and evaluate the appropriateness of these prescriptions based on clinical criteria and the impact this line of management has on the duration of their hospital stay. Methods: A total number of participants was n= 200 children, diagnosed as gastroenteritis. Demographic, clinical and antibiotic data were collected. SPSS version 21.0 was used in performing statistical analysis with p < 0.001 as the level of significance. Results: In 200 children with gastroenteritis (mean age 4.5 ± 2.3 years; weight 14.2 ± 4.1 kg), 50% had severe dehydration, 60% had fever, and 75% had vomiting. IV rehydration was required in 65%, with a mean hospital stay of 24.2 ± 5.5 hours. Inappropriate antibiotic use occurred in 75% of cases. Dehydration (OR = 3.50), fever (OR = 1.87), and inappropriate antibiotic use (OR = 2.75) significantly predicted IV rehydration (all p < 0.001). Dehydration and inappropriate antibiotic use also significantly prolonged hospital stay. Conclusion: Antibiotic prescription rates for pediatric gastroenteritis are extremely high and alarmingly, the majority of them are inappropriate.